Electrohydrodynamic air amplifier for low-energy airflow generation—An experimental proof-of-concept - Rubinetti, Donato; Iranshahi, Kamran; Onwude, Daniel; Nicolaï, Bart; Xie, Lei; Defraeye, Thijs (Frontiers in Energy Efficiency, 2023)
With electrohydrodynamics (EHD), we can propel air in a low-energy fashion. EHD airflow, or ionic wind, arises when a high voltage gradient is applied to a set of electrodes. The air ionizes between electrodes via corona discharge and accelerates in an electric field, exchanging momentum with the surrounding air. While the ionization process is energy-efficient, reaching competitive flow rates remains challenging from a high-voltage engineering perspective. To increase EHD-generated flow rates, this study experimentally investigates a novel concept called EHD air amplification. The concept uses ionic wind as bleed flow to induce a more significant bulk flow by the air-amplifying Coanda effect. Due to the complex interactions between EHD and dielectric structures for air amplification, the conceptual EHD air amplifier device is designed stage-wise, starting with a simple emitter-collector electrode configuration. First, regular EHD flow was studied in a 150×150×500 mm3 channel. Then, a dielectric material was added to determine its influence on the electric field. The impact of a converging nozzle on the EHD-generated airflow was subsequently studied. Lastly, the converged nozzle airflow was used to create a bleed flow on a plate to facilitate air amplification of the surrounding air. We show the proof-of-concept for an EHD air amplification system. After a voltage threshold of 14 kV, amplified airstreams up to an amplification factor of 3 were measured. Maximum airflow rates of about 15 m3 h-1 were obtained shortly before electric breakdown at 22 kV. Compared to regular EHD, we achieved a higher aerodynamic performance for the same electric energy invested. The flow rate to electric power ratio increased to 66 % in EHD air amplification compared to regular EHD. The proposed EHD air amplifier operates at atmospheric pressure. It lays the groundwork for further optimization studies to position EHD air amplification as a low-energy, low-maintenance, motor- and noiseless airflow generation technology.